High-Rise: European Lessons from Management and Maintenance (Global Journal of Management and Business Research, 2021)
High-rise buildings are extremely popular in Asia nowadays and high-rise seems to regain a new momentum in Europe and the Netherlands The failed high-rise wave of the 60s 70s of the last century with the Amsterdam Bijlmermeer as an all-time low caused an aftershock that lasted for many years More than two-thirds of the Bijlmer a high-rise district with 17 000 homes and over 40 000 inhabitants was demolished Wassenberg 2013 Bijlmermonitor Klundert 2014 Kleuver Soomeren 2009